Flows and Paradigms of Classical Muslim Figures' Thoughts on Education in Islam - Robitul Abror; Muhtadi Abdul Mun’im (Penerbit Hellow Pustaka, 2025)
This research explores the schools and paradigms of thought of classical Muslim figures regarding education in Islam, with a focus on Ibn Sina, Al-Farabi, and Al-Ghazali. Each figure makes a significant contribution to understanding education. Ibn Sina emphasized a holistic approach, where education aims to develop moral, physical and intellectual aspects in a balanced manner. Al-Farabi linked education to philosophy, emphasizing the important role of the state in creating an education system that supports individual and societal happiness. Meanwhile, Al-Ghazali focuses on moral and spiritual education, emphasizing that the main goal of education is the formation of character and closeness to God. These findings show that the thinking of this classical figure remains relevant in the context of modern education, where an approach is needed that not only prioritizes intellectual aspects, but also moral and spiritual aspects. This research is expected to contribute to the development of more holistic and sustainable Islamic education.